2014
DOI: 10.17159/2413-3051/2014/v25i2a2670
|View full text |Cite
|
Sign up to set email alerts
|

Use of hybrid solar-wind energy generation for remote area electrification in South-Eastern Nigeria

Abstract: This paper presents simulated hybridized solar-wind generation as an alternative for rural dwellers that do not have access to a conventional grid connection. Solar and wind were used as the main sources of energy with battery storage. Each power source has a DC-DC converter to control the power flow. An axial flux permanent magnet generator, which is suitable for a location with a low wind speed, was driven by the wind turbine. By using this generator, the efficiency of the system increased since certain loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Another possible configuration is wind-solar-BS (Atia and Yamada, 2016;Ahadi et al, 2016;Nnadi et al, 2014). The complementary nature of wind and solar in this configuration reduces the storage requirements and improves system availability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another possible configuration is wind-solar-BS (Atia and Yamada, 2016;Ahadi et al, 2016;Nnadi et al, 2014). The complementary nature of wind and solar in this configuration reduces the storage requirements and improves system availability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Its production covers a third of the world's energy consumption, which is mainly concentrated in thermal machines where combustion is on a large scale with the direct emission of millions of tons of CO2 causing high levels of pollution and global warming; and reduction of nature reserves [1].Renewable energy production techniques have evolved in terms of power and performance over the past decades. It has been used all over the world, especially in remote areas [2]. For economic reasons, the recent increase in oil prices obliges each country to choose the strategy of electric energy production, with an acceptable blow according to the possible wealth, and to exploit the sources of energy to the maximum.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cost of photovoltaic panels is reduced, which encourages investors to take charge. In particular that the availability of two sources of wind and solar energy, this gives us a sufficient argument to implement a hybrid source technology sufficiently mastered and managed to take major steps in the field of various applications and energy consumption, whose optimization of these systems will surely lead to a better use of solar and wind energy, in order to ensure the optimization control and operation of these systems which will surely lead to a better use of solar-wind energy [2]. A comparison has been made for many hybrid system optimization techniques [12] witch have been reported that could be applied to achieve a technologically optimal hybrid renewable energy system [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So solar can be used for power generation but even it has disadvantage that it is not available at night times and no power generation. So, using of single renewable source at a time may not meet the load requirement and so by combining these sources [2,3] they can be effectively used which leads to hybrid system. Standalone Hybrid power generation system [4][5][6] produces electrical energy with the use of more than one source and if one is not available another source can be used +for running the load.…”
Section: Introductionmentioning
confidence: 99%